Alpine open spaces in spatial planning: A plea for greater cross-border cooperation - Peter Haßlacher; Marco Pütz; Gero Nischik; Christoph Knauf; Marius Mayer; Hubert Job (Cross-border spatial development in Bavaria: Dynamics in cooperation - Potentials of integration, 2022)
Alpine open spaces are becoming noticeably scarcer. In the Alps, this applies to the inherently limited area of permanent settlement, which in the case of Tyrol covers only 11.8%. The population is growing in many of the valleys and with it the infrastructure it requires. However, the open spaces, situated at altitudes above the settlements, are also being successively broken up and exploited through technical facilities (e.g. cable cars, hydro-electric facilities) or increasingly intensive types of use (e.g. e-mountain bikes). The preservation of open spaces began in Bavaria as early as 1972 with the implementation of the Alpine Plan, which established spatial planning objectives. The Alpine Plan divided Bavaria's Alpine region into three zones of varying traffic intensity, a true legislative innovation. Zone C was intended for nature conservation, which was still in its infancy at that time, and also aimed to reduce natural Alpine hazards. Primarily, however, this planning initiative was related to the role of the landscape as a setting for recreation in open spaces, i.e. leisure and tourism activities in natural surroundings. Today, there are similar initiatives of varying success in South Tyrol (Italy), Austria and Switzerland. This paper aims to analyse, compare and describe these initiatives and to critically assess how they are formulated, how they work, and how they are implemented by planners. The focus is on comparing analyses of approaches for preserving open space for people (local residents and their traditional economic activities, but also visitors) and the natural heritage. Present-day regional and spatial planning practices related to Alpine open spaces in the Germanspeaking and Swiss Alpine regions are presented and critically evaluated and future options for harmonising approaches across the borders are discussed.
urn:nbn:de:0156-41580232; hdl:10419/253270; https://econpapers.repec.org/RePEc:zbw:arlabe:34
Keywords: 710; Alpine open spaces; GIS analysis; open space analysis; nature conservation; spatial planning; tourism